2010
DOI: 10.1103/physrevlett.105.207002
|View full text |Cite
|
Sign up to set email alerts
|

Angular Dependence of the Superconducting Transition Temperature in Ferromagnet-Superconductor-Ferromagnet Trilayers

Abstract: The superconducting transition temperature T(c) of a ferromagnet (F)-superconductor (S)-ferromagnet trilayer depends on the mutual orientation of the magnetic moments of the F layers. This effect has been previously observed in F/S/F systems as a T(c) difference between parallel and antiparallel configurations of the F layers. Here we report measurements of T(c) in CuNi/Nb/CuNi trilayers as a function of the angle between the magnetic moments of the CuNi ferromagnets. The observed angular dependence of T(c) is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 28 publications
7
96
0
1
Order By: Relevance
“…As we demonstrate in the analysis section of this paper, this minimum in T c arises from the enhanced long-range triplet pair amplitude in the maximally noncollinear configuration of the spin valve. We also note that our previous studies of the angular dependence of T c in NiFe/Nb/NiFe trilayers [32] found monotonic dependence of T c on α in the 0 to π range, which serves as indication of a much weaker triplet pair amplitude induced in the system with two ferromagnetic layer separated by a superconductor. This dependence is weak, which implies that (i) the pair amplitude decays slowly in the Cu spacer layer and (ii) the pair amplitude decays to nearly zero over the pinned layer thickness greater than 1.5 nm (the thinnest pinned layer employed in our studies).…”
Section: Angular Dependence Of T Csupporting
confidence: 54%
“…As we demonstrate in the analysis section of this paper, this minimum in T c arises from the enhanced long-range triplet pair amplitude in the maximally noncollinear configuration of the spin valve. We also note that our previous studies of the angular dependence of T c in NiFe/Nb/NiFe trilayers [32] found monotonic dependence of T c on α in the 0 to π range, which serves as indication of a much weaker triplet pair amplitude induced in the system with two ferromagnetic layer separated by a superconductor. This dependence is weak, which implies that (i) the pair amplitude decays slowly in the Cu spacer layer and (ii) the pair amplitude decays to nearly zero over the pinned layer thickness greater than 1.5 nm (the thinnest pinned layer employed in our studies).…”
Section: Angular Dependence Of T Csupporting
confidence: 54%
“…5,6 In this state, the real part of the order parameter penetrates the ferromagnet a distance on the order of the coherence length ξ F and oscillates due to dephasing by the exchange energy of the ferromagnet. This leads to the oscillations of the superconducting transition temperature (T c ) as a function of ferromagnet thickness [7][8][9][10][11] and π phase shift in S/F junctions. 12,13 Furthermore, recent measurements in S/F structures 11,[14][15][16] have provided evidence for triplet pairing in the ferromagnet induced by noncollinear magnetizations of the F layers.…”
Section: Introductionmentioning
confidence: 99%
“…T c reaches minimum if the relative magnetization is parallel and maximum for antiparallel magnetization. 27 A different behavior was observed for the FM/FM/SC nanostructures for which the critical temperature is minimized in case of perpendicular alignment of the magnetization.…”
Section: -21mentioning
confidence: 99%